2021
DOI: 10.3389/fpubh.2021.705354
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Health-Care Workers and Patients in Quarantine Wards: Evidence From a Survey of Frontline Health-Care Workers and Inpatients With COVID-19 in Wuhan, China

Abstract: Objective: Frontline health-care workers and patients with COVID-19 have been identified as high-risk groups for psychological problems. Experience of working or staying in quarantine wards generated psychological stressors for health-care workers and patients with COVID-19. The present study aimed to investigate the psychological symptoms of hospitalized patients with COVID-19 and the health-care workers treating them during the outbreak period, examine the effects of psychological stressors on mental health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…In addition, the study found that COVID-19 fear is associated with PTSD symptoms, which is consistent with previous literature [ 50 ]. This may be because health care workers facing COVID-19 infection develop COVID-19 fear, psychological distress, and severe concern about recovering their physical health [ 51 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the study found that COVID-19 fear is associated with PTSD symptoms, which is consistent with previous literature [ 50 ]. This may be because health care workers facing COVID-19 infection develop COVID-19 fear, psychological distress, and severe concern about recovering their physical health [ 51 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the study found that COVID-19 fear was an essential factor in post-traumatic stress disorder among health care workers, which is consistent with previous literature [45]. This may be because health care workers facing COVID-19 infection develop COVID-19 fear, psychological distress, and severe concern about recovering their physical health [46].…”
Section: Discussionsupporting
confidence: 87%
“…The epidemic of coronavirus disease 2019 (COVID- 19), originally occurred in Wuhan, Hubei, China, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread worldwide (1,2). As a public health emergency, COVID-19 is still an ongoing outbreak, and humans have been experiencing a relentless spread of variations of SARS-CoV-2 (3, 4), significantly undermining the domains of health, economy, environment, and society, unfortunately (5).…”
Section: Introductionmentioning
confidence: 99%
“…Given the fact that the transmission ability of COVID-19 is stronger and the incidence of mortality is relatively higher (6,7), rapid and accurate diagnostic methods show their great significance for the prevention, control, and management of COVID-19. Real-time fluorescence polymerase chain reaction (RT-PCR) remains the current gold standard for COVID-19 diagnosis (8); however, this diagnosis method has some shortcomings: (1) it is very time-consuming to obtain the results after sampling and may lead to experimental errors caused by manual handling (9, 10), (2) there are a high rate of falsenegative results (11), where there were even repeated negatives confirmed by other methods for patients when viral load is insufficient (12), (3) not all hospitals and clinics can implement these methods or the supply and quality of the reagents cannot keep up with the demand in time (13,14), (4) the severity, progression, and the evaluation of patients cannot be judged or traced (11,15,16). Compared to several limitations mentioned above, chest computerized tomography (CT), as a routine and powerful tool for diagnosing viral pneumonia, has the advantage of timeliness, celerity, and high stability and sensibility (17,18).…”
Section: Introductionmentioning
confidence: 99%